(untitled) (Педагогіка вищої та середньої школи, 2022)
The article is discovered content of the concept „civic consciousness” is defined the criterions and levels its forming. The initial level this quality is defined at students of the pedagogical university and correlation between the level forming of the civis consciousness and professional values of the future teacher.